2018
DOI: 10.1371/journal.pone.0190324
|View full text |Cite
|
Sign up to set email alerts
|

Association of atrial fibrillation and cancer: Analysis from two large population-based case-control studies

Abstract: BackgroundAn association between atrial fibrillation (AF) and risk of cancer has been suggested in several studies, including prospective cohort studies. However, the magnitude and the temporal nature of this association remain unclear.MethodsData from two large prospective population-based case-control studies, the Molecular Epidemiology of Colorectal Cancer (MECC, n = 8,383) and the Breast Cancer in Northern Israel Study (BCINIS, n = 11,608), were used to better understand the nature and temporality of a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 33 publications
2
48
0
7
Order By: Relevance
“…Six published observational articles were incorporated into the present analysis. [9][10][11][12][13][14] The integrated result demonstrated that patients with NOAF have a 24% increased risk of developing cancer. The subgroup analysis stratified by time interval, gender and type of cancer revealed the following: (1) the incident cancer significantly increased within 90 days after NOAF diagnosis, but not after that; (2) males appeared to have a higher risk, when compared to females; (3) the risk of lung cancer, but not colorectal cancer or breast cancer, was higher in patients with NOAF, when compared to non-AF patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Six published observational articles were incorporated into the present analysis. [9][10][11][12][13][14] The integrated result demonstrated that patients with NOAF have a 24% increased risk of developing cancer. The subgroup analysis stratified by time interval, gender and type of cancer revealed the following: (1) the incident cancer significantly increased within 90 days after NOAF diagnosis, but not after that; (2) males appeared to have a higher risk, when compared to females; (3) the risk of lung cancer, but not colorectal cancer or breast cancer, was higher in patients with NOAF, when compared to non-AF patients.…”
Section: Discussionmentioning
confidence: 98%
“…The funnel plot (Figure 4) presents the limited symmetry distribution of all the researches, with only one research randomly beyond 95% CI, which need to be examined. That is, the study conducted by Salibaet al 9 was the only case-control report, and was influenced by potential selection bias. The integrated result was optimized (RR: 1.35, 95% CI: 1.28-1.42, P<0.00001, I 2 =46%) after discarding the study conducted by Saliba et al 9…”
Section: 4sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A total of nine cohort studies (N = 670, 733) were included [8][9][10][11]. Summary of this selection process is given in PRISMA flow chart ( Figure 1).…”
Section: Studies and Patient Populationmentioning
confidence: 99%
“…Alternatively, studies also suggest that AFib could promote the development of cancer; as both Women's Health Study (WHS) and Danish National Registry study detected a significant increased risk of cancer after AFib diagnosis [9,10]. However, recent studies by Saliba et al, and Wassertheil-Smoller et al, paradoxically did not support the notion of AFib being a risk marker for cancer [11,12]. An increased risk of malignancy among patients with AFib would be of substantial public health importance, given the high prevalence and associated economic burden of both disorders.…”
Section: Introductionmentioning
confidence: 99%